1996
DOI: 10.1080/01919512.1996.10382853
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidant regeneration of granular activated carbon for controlling air‐phase VOCs

Abstract: The Pennsylvania State University is researching an advanced oxidation (AO) system for controlling volatile organic compounds (VOCs) (Cannon et al. 1994). The system includes an air-phase photolytic chamber, an air/water stripping tower, and granular activated carbon (GAC) beds, and the work herein describes he evaluation of the GAC beds. Field GACs have been evaluated, which had previously been loaded with VOCs and regenerated with AO for several years at several full scale installations. Full scale response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…and, for all practical purposes, was completely removed by 3 in. 28 This penetration became greater with prolonged exposure of the dry GAC bed to O 3 and AO.…”
Section: Mechanism Of O 3 /Ao Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…and, for all practical purposes, was completely removed by 3 in. 28 This penetration became greater with prolonged exposure of the dry GAC bed to O 3 and AO.…”
Section: Mechanism Of O 3 /Ao Enhancementmentioning
confidence: 99%
“…The reasons for this enhanced removal stems both from (1) the ability of the AO and O 3 to convert a fraction of the MIBK to smaller and more oxygenated byproducts, and (2) the influence that AO and O 3 have in causing MIBK to desorb from the GAC surface. 25,27,28 These features are limited by the extent to which O 3 and AO can penetrate into the GAC bed.…”
Section: Mechanism Of O 3 /Ao Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Hwang et al 12 examined the use of ozonation in addition to granular activated carbon adsorption and aerated biofilters for removing dissolved odorous compounds in wastewater. Cannon et al 13 and Dusenbury and Cannon 14 reported regeneration of activated carbon for volatile organic compound (VOC) control by an advanced oxidation process utilizing hydroxyl radicals originating from ozone. The reaction of ozone with H 2 S in the air phase is expressed by the following equation: 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, TGA has been used to determine reaction rate and to establish kinetic models during the pyrolysis of waste tires 17 and both the adsorption rate and the kinetic models of volatile organic compounds by activated carbon. 18 However, the use of TGA to investigate the adsorption by activated carbon of heavy metals is uncommon. Therefore, this study aimed to apply the TGA technique to measure the adsorptive capacity of HgCl 2 (which is the predominant species of mercury emitted from MSW incinerators) on PAC, to evaluate the influence of adsorption temperature on the adsorptive capacity of PAC, and to investigate the adsorption isotherms of HgCl 2 on PAC.…”
Section: Introductionmentioning
confidence: 99%